Pengaruh Faktor Lingkungan terhadap Kejadian Multidrug-Resistant (MDR) di Kabupaten Jember - Thahri Iskandar; Febri Endra Budi Setyawan; Djaka Handaja; Nurlayli Hidayati Husein (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Tuberculosis is a chronic and contagious infectious disease caused by Mycobacterium tubeculosis. In terms of TB treatment, it still can’t be handled optimally, but there is a new problem namely Multidrug –Resistant which is now a global problem in various worlds. In Jember Regency, the detection of Multidrug –Resistant TB cases was known to increase rapidly in 2018. In the occurrence of a disease, according to H.L Blum (1981), there are 4 main factors the occurance of a diseas: lifestyles, environment, health care services, and pshycobiology. Environment have the biggest role out of those factors.This study to analyze the relationship between environmental factors and the incidence of Multidrug –Resistant Pulmonary TB patients in Jember Regency.This study used SEM –PLS (Structural Equation Modeling –Partial Least Square) correlation test. The samples are collected using area sampling method and the sample size is determined using Slovin’s formula becausethe population size is already known (144 respondents). Questionnaire that has been tested for validity is used as measuring instrument in this research.Based on the analysis of the SEM –PLS (Structural Equation Modeling –Partial Least Square) program which was carried out in a multigroup analysis of environmental factors.The Outer Model shows that the loading factor of occupancy density, family and job’s values is >0,6. Furthermore, the inner model shows that t-count of physical variables in MDR –TB cases is higher than the t-table(1,96). The results of the structural model for SEM –PLS analysis indicate a relationship between the occupancy density of the physical environment variables and the incidence of MDR –TB.There is a relationship between occpancy density in physical environment variables and the incidence of MDR –TB in Jember Regency.